Optimization of Eco-Friendly Materials in Urban Road Construction to Support Sustainable Development and Energy Efficiency - Robert, Robert; Lantang, Evayanti Tirtania (Jurnal Ar Ro'is Mandalika (Armada), 2025)
The rapid pace of urbanization has increased the demand for environmentally friendly and energy-efficient urban road infrastructure. However, the use of conventional construction materials contributes to ecosystem degradation and carbon emissions. This study aims to optimize the use of eco-friendly materials in urban road construction to support sustainable development and energy efficiency. A qualitative literature review approach was employed to examine relevant scientific sources, including journals, books, and policy documents. The data were analyzed using content analysis to identify patterns and the contributions of eco-friendly materials to energy efficiency and carbon emission reduction. The findings indicate that materials such as recycled concrete, eco-friendly asphalt with bio-based binders, and pollution-absorbing paving materials have significant potential in enhancing energy efficiency and reducing carbon emissions in urban road construction. Several cities, including Tokyo, Los Angeles, and Paris, have begun adopting these approaches in their infrastructure projects. This study recommends the adoption of recycled materials, bio-based binders, and eco-friendly paving technologies as key strategies in developing sustainable road infrastructure. The practical implications of this research include long-term energy savings, reduced maintenance costs, and improved urban environmental quality.